Stock prices and top management changes - Warner, Jerold B.; Watts, Ross L.; Wruck, Karen H. (Journal of Financial Economics, 1988)
This paper studies the association between a firm's stock returns and subsequent top management changes. Consistent with internal monitoring of management, there is an inverse relation between the probability of a management change and a firm's share performance. This relation can result from monitoring by the board, other top managers, or blockholders. However, unless share performance is extremely good or bad, logit models have no predictive ability. No average stock price reaction is detected at announcement of a top management change.